Stereotip Gender di Media: Representasi Atlet Angkat Besi Perempuan pada Drama Weightlifting Fairy Kim Bok Joo - Lailatur (Universitas Islam Balitar, 2021)
Gender stereotype being the important problem if it causes discrimination againts stereotyped objects, both men and women. Gender stereotype cannot be separated by the culture that constructed the stereotypes themselves, such as women stereotype. Stereotype attached to women that are women identic with beauty, gentle, cowardly, and suitable work at home or as household. Movie or drama as the one of mass communication which have role on build public opinion. Therefore, media have the important role to manage the public opinion on women stereotype. The goal of this research to analysis how the women stereotype which is represented by female weightlifter in drama “Weightlifting Fairy Kim Bok Joo”. The method of this research used qualitative method and used semiotic approach to analyze the meaning of the picture in each scene in the drama. To collect the data researcher used documentation from scene in the drama and used literature review to sanction the research data. the result of this research showed that through the representation of female weightlifters in the drama “Weightlifting Fairy Kim Bo Joo” brought up the stereotype that women had the side of courage, cannot be underestimate, ambitious, and can work in male shutter.